PENGARUH DISKUSI KELOMPOK TERBIMBING TERHADAP HASIL BELAJAR GEOGRAFI MATERI DINAMIKA KEPENDUDUKAN INDONESIA PADA SISWA KELAS XI IPS SMA N 1 2X11 KAYUTANAM - Tiara Azura; Nofrion Nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This article is motivated by the number of teachers who still use the lecture method of learning or often called the conventional method so that the learning process becomes less effective. The main purpose of this study was to determine the effect of the guided group discussion learning model on the geography learning outcomes of class XI students at SMA N 1 2X11 Kayutanam. The method used in this research is quantitative research with a quasi-experimental type of research (Quasi Experimental). The results of hypothesis testing carried out using a t-test with a significance level of 0.05, the obtained tcount ttable is 2.076 2.01. The results of the pre-test showed that the two classes had similar initial abilities, namely 69.72 in the control class and 69.2 in the experimental class. the post-test results showed that the experimental class got a higher average than the control class, which was 80.2 and the control class with an average score of 76.